Environmental changes recorded in the Holocene sedimentary infill of a tropical estuary. (20th May 2018) - Kumar, Mukesh; Boski, Tomasz; Lima-Filho, Francisco P.; Bezerra, Francisco H.R.; González-Vila, Francisco J.; González-Pérez, José A.
Abstract: Early-to late Holocene sedimentary infill of the Potengi-Jundiai Estuary (Brazil) was studied in a 31.5 m long sediment core. The borehole was drilled in a mangrove area within the central part of the flood tide delta. The sedimentary record, encompassing the last 10 kyr, was studied for sediment texture and for the n -alkanes composition of organic matter (OM). Sediments rich in OM and bivalve shells accumulated during the period of sea-level rise, mostly in an intertidal environment of mangrove forest, mudflat and subtidal estuarine flood delta. The characterization of n -alkanes (C10 -C33 ) and lignin methoxyphenols by means of direct analytical pyrolysis (Py-GC/MS) technique allowed determining the sources of the extant OM. Downcore fluctuations were observed in n -alkanes and in several n -alkane based indices, such as long chain carbon preference index (CPI C24 -C33 ), long to short chain ratio (L/S) and average chain length (ACL), as well as in the relative proportion of lignin derived compounds. The n -alkanes distribution points to changing sources of OM input to the estuarine sediments over most of the Holocene period. Major inputs of terrestrial vegetation alternated with periods of mixed input from aquatic macrophytes as the rate of sea-level rise changed over time. The n -alkanes distribution and the lignin markers were useful for reconstructing paleoenvironmental conditions, particularly during the early Holocene when the lower Potengi River valley (now an estuarine area) could accommodate terrestrial forest vegetation before switching to halophytic mangroves as sea levels rose.